Cross-Script Phonological Activation in Chinese--English Bilinguals: The Effect of SOA From Masked Priming. - Ge Xu; Jiexuan Lin; Yanping Dong (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2021)
The issue of bilingual phonological access remains unclear for bilinguals with cross-script language systems, which is especially true when the time course of phonological activation is involved. To investigate the time course of cross-script phonological activation, the present study asked Chinese-English bilinguals to complete a word naming task that was conducted in a forward-masked phonological priming paradigm in three stimulus onset asynchrony (SOA) conditions. By comparing the interlingual and intralingual phonological priming effects in a within-subjects design, we found that (a) target naming in Chinese and English was facilitated by a phonologically similar English or Chinese prime in the three SOA conditions (43 ms, 75 ms, and 150 ms) and the facilitation effect of the prime reached the peak when the pronunciation of the prime--target pair most resembled each other and (b) manipulation of the SOAs affected both the naming latencies of target words and the sizes of the phonological priming effect. In particular, naming latencies in each prime--target type displayed an increasing tendency as the SOA prolonged. Moreover, despite the varied sizes of the priming effect in the three SOA conditions, we found a consistent pattern that the priming effects in two interlingual conditions resembled their respective intralingual conditions along the time course. Taken together, these findings provide strong support for an integrated phonological representation of bilinguals and further extend the language nonselective access hypothesis to language pairs with very different orthographic systems. Implications for the manipulation of the SOAs in the masked priming paradigm are also discussed.